2018
DOI: 10.1016/j.pjnns.2018.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Future challenges of stroke treatment

Abstract: Posterior circulation stroke accounts for approximately 20% of all ischaemic strokes. Acute basilar artery occlusion (BAO) is one of the most severe conditions, it is associated with death or major disability in more than three quarters of the cases, and its optimal management remains unestablished. Currently, the treatment is based primarily upon consensus, the clinical practice varies widely, and the actual benefit of mechanical thrombectomy has to be fully estimated. Although the recent years have profoundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…The number of AIS patients treated by means of IVT or MT has increased significantly in recent years [7][8][9]. As shown in other studies [10][11][12][13][14][15][16], we found that MT used to treat AIS in anticoagulated patients did not change long-term outcomes compared to non-coagulated AIS patients treated by MT.…”
Section: Discussionsupporting
confidence: 74%
“…The number of AIS patients treated by means of IVT or MT has increased significantly in recent years [7][8][9]. As shown in other studies [10][11][12][13][14][15][16], we found that MT used to treat AIS in anticoagulated patients did not change long-term outcomes compared to non-coagulated AIS patients treated by MT.…”
Section: Discussionsupporting
confidence: 74%
“…The prospects for effective therapeutic targeting of MMPs require the establishment of conditions to specifically modulate a given MMP isoform, or a subset of MMPs, in a given spatio-temporal context [131]. Further research is warranted to better understand the interactions between MMPs and their molecular and cellular environments, determine the optimal timing of MMPs inhibition for achieving a favorable therapeutic outcome, and implement the discovery of innovative selective agents to spare harmful effects before therapeutic strategies targeting MMPs can be successfully incorporated into routine practice [132,133].…”
Section: Clinical Implications and Future Perspectivesmentioning
confidence: 99%
“…Despite advances in modern medicine and medications, stroke remains a burden affecting disability-adjusted life years ( 2 ). Strokes can cause significant impairments that include different degrees of cognitive and behavioral dysfunction, paralysis, dysphagia, aphasia, and motor dysfunction ( 3 ). The mortality rate of stroke has been gradually decreasing, but the disability rate of stroke remains high ( 4 ).…”
Section: Introductionmentioning
confidence: 99%